Impact of Social Media Misinformation on its Users Regarding Vaccination, Prevention, and Treatment of COVID-19 - Akasha Masud; Bushra Mushtaq; Anum Abdullah; Hafiza Arooj Waqar; Hina Shahid; Najjam-us-Sehar; Soha Mobeen; Rabia Riaz; Diva Bibi (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Abstract Background: COVID-19 is a mild to severe respiratory illness caused by a coronavirus characterized mainly by fever, cough and shortness of breath and may progress to pneumonia and respiratory failure. It has been observed that social media users were influenced by the misinformation spread through it. Objective: To determine the effect of misinformation on social media regarding vaccination, prevention, and treatment of COVID-19, among inhabitants of Rawalpindi and Islamabad. Materials and Methods: A descriptive cross-sectional study was carried out among 406 participants who were active social media users for at least 6 months prior to the start of the study i.e., November 2020 to April 2021. They were included in the study by convenience sampling. The study was conducted by students of Rawalpindi Medical University at specific areas of Rawalpindi and Islamabad. A structured questionnaire was filled by the participants in which they were asked about age, marital status, education, views on the utility of information found on social media about COVID-19 and whether they crosschecked information collected through social media about COVID-19. Information was also collected regarding the use of masks, social distancing and vaccination status. Data were entered and analyzed through SPSS version 25. Results: Out of 406 people, 350 (86.2%) were active social media users and 56 (13.8%) were using social media occasionally. 322 (79.3%) were vaccinated against COVID-19 and 84 (20.7%) were not vaccinated. 317 (78.1%) heard false news on social media regarding COVID-19 and 296 (72.9%) obtained misinformation regarding the SARS-Cov-2 virus. About 199 participants (49%) cross-checked the information that they received from social media. The number of people who practiced social distancing, wore a mask and, read tweets about COVID-19 on social media was 164 (40.4%), 312 (76.8%), and 282 (69.5%) respectively. Conclusion: The majority of people got vaccinated against COVID-19. The study population was more aware, and most of them could differentiate between actual and false news on social media by verifying it. The reach of misinformation about COVID-19 was found to be extensive among social media users. Key words: Social media findings, COVID-19, misinformation.